2007
DOI: 10.1097/id.0b013e3180312323
|View full text |Cite
|
Sign up to set email alerts
|

Bifid Mandibular Canal in Japanese

Abstract: The location and configuration of mandibular canal variations are important in surgical procedures involving the mandible, such as extraction of an impacted third molar, dental implant treatment, and sagittal split ramus osteotomy. We report 3 Japanese patients with bifid mandibular canals using panoramic radiograph and multi-slice helical computed tomography (CT) images. In 2 of the 5 sides, the bifid mandibular canal was suggested on panoramic radiograph. The bifid mandibular canal had a short and narrow upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 13 publications
(12 reference statements)
3
39
0
1
Order By: Relevance
“…Owing to the two-dimensional nature of PANs, the upper airway, soft palate and uvula, and opposing side and submandibular fossae may produce ghost shadows and interfere with the visualization of neurovascular canals. The present study found a visualization rate of BMCs using PANs as compared with that using CBCT of 37.8%, which was similar to the rate previously reported by Naitoh et al 31 Neves et al, 34 by contrast, reported a 76% visualization rate, but, this may be owing to the low number of BMCs that they detected on CBCT. Bogdán et al 35 found 19.6% of BMCs in dry mandibles, but only 0.2% of total cases were visible on PANs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Owing to the two-dimensional nature of PANs, the upper airway, soft palate and uvula, and opposing side and submandibular fossae may produce ghost shadows and interfere with the visualization of neurovascular canals. The present study found a visualization rate of BMCs using PANs as compared with that using CBCT of 37.8%, which was similar to the rate previously reported by Naitoh et al 31 Neves et al, 34 by contrast, reported a 76% visualization rate, but, this may be owing to the low number of BMCs that they detected on CBCT. Bogdán et al 35 found 19.6% of BMCs in dry mandibles, but only 0.2% of total cases were visible on PANs.…”
Section: Discussionsupporting
confidence: 90%
“…To be of assistance in identifying suspected BMCs, a distinctive radiographic feature has The present study involves a large sample and found that the rate of visualization of BMCs on PANs as compared with CBCT was similar to the results reported by Naitoh et al 31 Kuribayashi et al 7 explained that buccolingual canals can be easily detected on CBCT but might be missed on PANs. However, in the present study, the proportion of buccolingual canals was very low, suggesting that features other than the canal type must also play a role.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, the course of the mandibular canal, such as the bifurcation and anterior loop, multiple mental foramina, mandibular incisive canal, and lingual foramen have been assessed using helical computed tomography (CT) and cone-beam computed tomography (CBCT) images [1][2][3][4][5][6][7][8] . Jacobs et al (2002) 7) reported that the lingual foramen could be detected in 82% of cases using spiral CT scan images for the preoperative planning of implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…There are various classifications for bifid mandibular canals proposed by different authors such as Langlais et al, [5] Nortjé et al, [8] and Naitoh et al [14] In the present study, Langlais et al, classification was utilized to designate the type of bifid mandibular canal since it was the most cited classification system in the literature.…”
Section: Discussionmentioning
confidence: 95%